An Exploratory Study of Food Waste in the Hospitality Industry of Pokhara - Ranabhat, Anita (Journal of Interdisciplinary Studies, 2024)
One-third of the global food production is wasted globally. Food production is a resource intensive process and safe disposal of food wasted requires additional resources. In tourism industry food is just more than fulfillment of basic needs. Food is linked with the experience. Food wastage in hospitality is accepted as a major challenge with multifaced consequences and awareness to address the issue of food waste is also increasing. In the context of developing countries like Nepal the topic is still under-studied. Therefore, this study is focused on owners and managers perspective on food wastage in tourism industry of Pokhara with the objectives of identifying current composition and causes of food waste and established approaches to mitigate it. This study was carried out with key informants’ in-depth interview and on-site observations. Unrealistic expectations, unsustainable consumption patterns, lack of general public awareness and management limitations on wastage controlling were major themes identified by the study. The findings call for quantitative study in mass scale to know the exact situation of the food waste in hospitality industry of Pokhara.